Validating a dietary approach to determine amino acid:lysine ratios for pigs - Marcio Antonio Dornelles Goncalves; Michael D Tokach; Steven S Dritz; K J Touchette; Joel M DeRouchey; Jason C Woodworth; Robert D Goodband (Kansas Agricultural Experiment Station Research Reports, 2014)
Standardized ileal digestible (SID) amino acid:lysine (AA:Lys) ratio experiments are commonly conducted to estimate the AA requirement of pigs relative to lysine (Lys) and allow for accurate diet formulation. The objective of the studies herein was to validate a dietary approach to determine the optimal SID AA:Lys ratio for pigs using tryptophan (Trp) as a model. Four 21-d experiments were conducted in which pigs (337 × 1050; PIC) were fed corn-soybean meal—based diets with 30% corn dried distillers grains with solubles (DDGS). A total of 1,188, 1,232, 1,204, and 1,183 pigs with initial BW of 28.5 ± 0.4, 50.1 ± 1.3, 127.0 ± 2.5, and 192.5 ± 2.6 lb were used in experiments 1, 2, 3, and 4, respectively. Each experiment had 11 pens per treatment with 24 to 28 pigs per pen. In Experiment 1, each pen housed the same number of barrows and gilts, whereas in Experiments 2 to 4 only gilts were used. Dietary treatments were: (1) High CP, High Lys, and High Trp:Lys ratio (HHH); (2) Low CP, High Lys, and High Trp:Lys ratio (LHH); (3) Low CP, Low Lys, and High Trp:Lys ratio (LLH); and (4) Low CP, Low Lys, and Low Trp:Lys ratio (LLL). The SID Trp concentrations used were 14.5 vs. 20% of Lys, CP was at least 3 percentage units different, and SID Lys levels were 0.01 percentage unit above the estimated requirement at the expected initial BW and 0.10 or 0.05 percentage units below requirement at the expected final BW of the Experiment 1 (nursery) and Experiments 2, 3, and 4 (finishing), respectively. In Experiment 1, decreasing CP (HHH vs. LHH) did not influence ADG but increased (P<0.05) F/G. Decreasing Lys (LHH vs. LLH) and decreasing the SID Trp:Lys ratio (LLH vs. LLL) reduced (P<0.05) ADG and increased (P<0.05) F/G. In Experiment 2, decreasing CP (HHH vs. LHH) did not affect ADG but increased (P<0.05) F/G. Decreasing Lys (LHH vs. LLH) and the SID Trp:Lys ratio (LLH vs. LLL) decreased (P<0.05) ADG and increased (P<0.05) F/G. In Experiment 3, decreasing CP (HHH vs. LHH) or Lys (LHH vs. LLH) did not influence ADG or F/G. Decreasing the SID Trp:Lys ratio (LLH vs. LLL) reduced (P<0.05) ADG and increased (P<0.05) F/G. In Experiment 4, decreasing CP (HHH vs. LHH) did not influence ADG but increased (P<0.05) F/G. Decreasing Lys (LHH vs. LLH) had no effect on performance, but decreasing the SID Trp:Lys ratio (LLH vs. LLL) reduced (P<0.05) ADG and increased (P<0.05) F/G. In conclusion, low-CP diets formulated 0.10 and 0.05 percentage units below the SID Lys requirement at the end of the experiment's weight range appear to ensure pigs are below their Lys requirement when determining the optimal SID Trp:Lys ratio for 29- to 52-lb and 50- to 80-lb pigs, respectively. For pigs heavier than 80 lb, formulating diets at 0.05 percentage units below the SID Lys requirement at the end of the experiment's weight range can limit the ability to provide statistical evidence that pigs are under their lysine requirement.; Swine Day, Manhattan, KS, November 20, 2014
Keywords: Swine Day; 2014; Kansas Agricultural Experiment Station contribution; no. 15-155-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1110; Amino acid ratio; Lysine; Tryptophan